Avenoir [compact disc] - Scott, Calum (Capitol Records, 2025)
With his powerful voice and soul-baring songwriting, Calum Scott creates the kind of deeply resonant songs primed to accompany the most meaningful moments in our lives. Since his breakthrough single "You Are The Reason," the UK-based artist has heard from countless fans across the globe who've turned to his music as a soundtrack for major life events or solace in enduring tremendous heartbreak and loss. His third album features the singles, "Roots," "Lighthouse," At Your Worst," My World," and God Knows," a stunning collection of songs that form a heartfelt plea to live life to its fullest.